Resistance of coconuts in St. Lucia to attack by the coconut mite Eriophyes guerreronis Keifer - Moore, D.; Alexander, L.
Some Cocos nucifera were very susceptible, others relatively resistant. Two easily noted features, rounded nuts and dark green nuts, were associated with less attack than occurred on other nuts. There appear to be good possibilities of selecting mite-resistant and productive trees. Resistance of coconuts in St Lucia to attack by the coconut mite Eriophyes guerreronis Keifer.
Keywords: COCONUT